Esoteric Buddhism at Dunhuang : rites and teachings for this life and beyond - Kapstein, Matthew; Van Schaik, Sam (Brill's Tibetan studies library ;, 2010)
Esoteric Buddhism in late first millennium Tibet and China is nowhere in evidence so clearly as in materials from Dunhuang. In the original contributions presented here, Robert Mayer and Cathy Cantwell examine the consecrations of the wrathful divinity VajrakAlaya, while Sam van Schaik considers approaches to the vows of tantric adepts. Philosophical interpretations of MahAyoga inform Kammie Takahashia (TM)s study of the a ~Questions of Vajrasattvaa (TM). The background for later Tibetan tantric mortuary rites are examined in chapters by Yoshiro Imaeda and Matthew Kapstein. In the closing chap.